1996
DOI: 10.1152/ajprenal.1996.270.1.f192
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of calcium oxalate monohydrate crystals to anionic sites on the surface of renal epithelial cells

Abstract: Adhesion of microcrystals to the apical surface of renal tubular cells could be a critical step in the formation of kidney stones. The role of membrane surface charge as a determinant of the interaction between renal epithelial cells (BSC-1 line) and the most common crystal in kidney stones, calcium oxalate monohydrate (COM), was studied in a tissue culture model system. Adhesion of COM crystals to cells was blocked by cationized ferritin. Other cations that bind to cells including cetylpyridinium chloride and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 0 publications
1
96
0
Order By: Relevance
“…However, binding of microcrystals to the apical surface of tubular cells (5,11) or perhaps nucleation on the cell surface (36) followed by cellular processing of the crystals (11,37) could be important determinants of intranephronal calcification. Our study supports the hypothesis that injury of tubular cells favors crystal deposition (33) and possibly promotes kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, binding of microcrystals to the apical surface of tubular cells (5,11) or perhaps nucleation on the cell surface (36) followed by cellular processing of the crystals (11,37) could be important determinants of intranephronal calcification. Our study supports the hypothesis that injury of tubular cells favors crystal deposition (33) and possibly promotes kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…One hour later, the buffer was aspirated and replaced with DMEM that contained 5% calf serum. 2 , 0.5 mM MgCl 2 , 5.6 mM glucose) at 38°C as described previously (5). Preliminary experiments defined these enzyme concentrations as having maximal effects on crystal binding without being cytotoxic.…”
Section: Uric Acid and Uric Acid Crystal Treatment Of Monolayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies showed that COM crystals, which are the predominant form of CaOx occurring in human kidney stones (41), are highly membranolytic (55), and also that their adherence to renal epithelial cells is very rapid, concentration dependent, and significantly greater than crystals of other calcium minerals (33, 36 -37). COM crystals were also shown to adhere to anionic sites on the surface of renal epithelial cells (32), while their attachment was altered by manipulating either cell surface characteristics and/or concentrations of soluble proteins and anions in the culture medium (31)(32)(33)54). Furthermore, in cell lines with properties similar to those of proximal tubules, adhesion of crystals was followed by their internalization and subsequent dissolution, which took 5-7 wk (34).…”
mentioning
confidence: 99%
“…In addition, it appears mathematically unlikely that nucleation and growth of an individual crystal could produce a particle large enough to occlude a nephron lumen (4). Therefore, our laboratory (5)(6)(7)(8)(9)(10)(11) and others (12)(13)(14)(15)(16)(17) have investigated the mechanism(s) whereby urinary crystals can interact with renal epithelial cells; once adherent to a cell, smaller particles could be retained and serve as a nidus for renal stone formation.…”
mentioning
confidence: 99%